The Theory of Sales: A Simple Model of Equilibrium Price Dispersion with Identical Agents - Stiglitz, Joseph E.; Salop, Steven C. (American Economic Review, 1982)
The article examines equilibrium in a competitive market in which the mythical auctioneer is absent and information is costly to gather. As a result, individuals may not be perfectly informed about prices or qualities of what is being sold. According to the author, equilibrium in such markets may differ markedly from the one conventionally studied by neoclassical theory. In particular, the only market equilibrium may be characterized by price dispersion for a homogeneous commodity, the law of the single price does not obtain. The article illustrates this with a model in which all individuals are identical and in which there is no exogenous source of noise, no external disturbances to the market, which have to be equilibrated. In the model, although all individuals have identical preferences and incomes and all firms have identical technologies, some firm charge high prices and others charge low prices. High-price stores earn a larger profit per sale, but make fewer sales. Equilibrium entails equal profits for two kinds of stores, that is, the lower volume of high-price stores exactly compensates for the higher profit per sale. The model that is developed by authors is of interest not only for the insight that it provides into the nature of price dispersion in the economy, but also because it provides at least a partial explanation of some aspects of retailing which otherwise would be difficult to explain.